2012
DOI: 10.1016/j.vetimm.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization of the African clawed frog (Xenopus laevis) upregulates the mucosal immunoglobulin IgX

Abstract: The frog Xenopus laevis is a model species for developmental biology but is also of significant interest to comparative immunologists. Amphibians are the oldest group of organisms in which both the B lymphocytes of some species undergo immunoglobulin (Ig) class switch recombination and also have a dedicated mucosal Ig isotype. The purpose of this study was to test the hypothesis that frog IgX would be produced in response to oral immunization. In order to facilitate studies of humoral, and especially mucosal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…As more immunoglobulins were cloned, however, it became clear that IgX is orthologous to IgA, re-estimating the emergence of this isotype to the origins of tetrapods 169 . IgX levels increase after immunization with mucosal antigens 170 . In addition, unlike IgY but similar to mammalian IgA, switching to IgX can occur in the absence of T cells.…”
Section: Mucosal Immunitymentioning
confidence: 99%
“…As more immunoglobulins were cloned, however, it became clear that IgX is orthologous to IgA, re-estimating the emergence of this isotype to the origins of tetrapods 169 . IgX levels increase after immunization with mucosal antigens 170 . In addition, unlike IgY but similar to mammalian IgA, switching to IgX can occur in the absence of T cells.…”
Section: Mucosal Immunitymentioning
confidence: 99%
“…For example, antibodies analogous to IgM will undertake these roles in some cases, whereas in others alternative Ig isotypes have evolved such as IgX in amphibians (Du et al, 2012) and IgT in teleost fish (Zhang et al, 2010).…”
Section: Iga Heavy Chain Genesmentioning
confidence: 99%
“…Recently, it was revealed that in contrast to intracoelomic injection, oral immunization of antigen in frogs induces IgX in plasma (59). In contrast, following intraperitoneal immunization with DNP, specific anti-DNP IgM and IgY, but not IgX, were significantly induced in serum (55).…”
Section: Amphibian B Cellsmentioning
confidence: 99%